Physicians as Mediators of Health Policy: Acceptance of Medicaid in the Context of Buprenorphine Treatment - Knudsen, Hannah K. (J Behav Health Serv Res, 2019)
Increasing numbers of individuals with opioid use disorder (OUD) are insured by Medicaid. Little is known about whether providers of buprenorphine, an evidence-based OUD pharmacotherapy, accept this type of payment. Data are scant regarding whether Medicaid acceptance varies by physician and state-level characteristics. To address these gaps, national survey data from 1,174 buprenorphine-prescribing physicians (BPPs) and state characteristics were examined in a multi-level model of Medicaid acceptance. Only 52.0% of BPPs accepted Medicaid for buprenorphine-related office visits. Specialists in addiction and psychiatry were significantly less likely to accept Medicaid than other specialties, as were BPPs delivering buprenorphine in individual medical practice. Perceived adequacy of Medicaid reimbursement was positively associated with accepting Medicaid. Medicaid acceptance was not associated with states’ implementation of the Medicaid expansion. Individuals who are covered by Medicaid may face barriers to accessing buprenorphine treatment, which has high public health significance given the ongoing opioid epidemic.